Etnogastronomi Ayam Napinadar: Simbolisme dan Filosofi Kuliner Tradisional dalam Upacara Adat Masyarakat Batak Toba di Laguboti - Natasya Sara Apriza Siahaan; Shelly Marcella Mendrofa; Naufal Rizki; Dimas Hidayat; Esi Emilia; Jenri P Hutasoit; Reny Yuliana Siahaan (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to examine the gastronomy of the traditional culinary dish Ayam Napinadar as part of Batak cultural identity, covering aspects of history, ingredients, processing techniques, cultural values, and preservation challenges. The background of this research is based on the importance of maintaining the sustainability of traditional cuisine amid modernization and changes in consumption patterns. The method used is a qualitative approach through in-depth interviews with three informants, namely an MSME (Micro, Small, and Medium Eterprises) practitioner, a traditional leader, and a consumer. The results show that Ayam Napinadar has a unique characteristic in the use of andaliman and blood (gota) as its distinctive flavor. Traditionally, the cooking process involves grilling over firewood to produce a characteristic smoky aroma, although it has now shifted to more practical methods without altering the original recipe. From a cultural perspective, Ayam Napinadar holds symbolic meaning as an expression of prayers, blessings, and joy in various Batak traditional ceremonies. However, there are challenges in its preservation, such as the declining participation of younger generations in traditional activities and the increasing influence of modern foods. In conclusion, Ayam Napinadar functions not only as food but also as a medium for preserving cultural values and ethnic identity. This study provides benefits as a basis for developing gastronomic tourism and strategies for preserving traditional cuisine through education, collaboration, and the use of modern promotional media.